Reluctant taxonomies: biology as paradigm in Margaret Drabble's fiction. Issue 4 (21st April 2018) - Campos, Liliane
ABSTRACT: This article examines the metaphorical and metanarrative role of biology in Margaret Drabble's recent fiction. From the metaphor of natural selection in her social anatomies of the 1980s ( The Radiant Way, A Natural Curiosity ) to the central questions of nature and nurture, genetics and environment in more recent novels ( The Peppered Moth, The Sea Lady and The Pure Gold Baby ), biology plays a key part in Drabble's portrayal of social and psychological determinisms. I argue that these analogies express an underlying taxonomic anxiety – a narrative negotiation and increasingly ironic classification of characters and novels according to types. Biology emerges as both a figurative space and a discourse whose power can be resisted and diverted. After demonstrating the recurrent analogy between scientific observation and the narrative gaze, the study divides the five novels into two periods. In the first group, I highlight the characters' attempts to escape the maternal type, and the paradoxical endorsements of this struggle by the narrative voice. In the second, I examine the implication of biological and medical paradigms for narrative form, from the nostalgic relation to Romantic organicism in The Sea Lady to the structural implications of disabled diagnosis in The Pure Gold Baby .